Weak decays of $${\varvec{B}}_{{\varvec{c}}}$$ B c involving vector mesons in self-consistent covariant light-front approach - Thejus Mary S.; Avijit Hazra; Neelesh Sharma; Rohit Dhir (European Physical Journal C: Particles and Fields)
Abstract We present a comprehensive analysis of weak transition form factors, semileptonic decays, and nonleptonic decays of $$B_c$$ B c mesons involving pseudoscalar (P) and vector (V) mesons for bottom-conserving and bottom-changing decay modes. We employ the self-consistent covariant light-front quark model (CLFQM), termed type-II correspondence, to calculate the $$B_c$$ B c to P(V) transition form factors. The type-II correspondence in the CLF approach gives self-consistent results associated with the $$B^{(i)}_j$$ B j ( i ) functions, which vanish numerically after the replacement $$M^{′ (′ ′ )} → M_0^{′ (′ ′ )}$$ M ′ ( ″ ) → M 0 ′ ( ″ ) in traditional type-I correspondence, and the covariance of the matrix elements is also restored. We investigate these effects on bottom-conserving $$B_c$$ B c to P(V) form factors that have not yet been studied in CLFQM type-II correspondence. In addition, we quantify the implications of self-consistency propagating to weak decays involving both bottom-conserving and bottom-changing $$B_c$$ B c transition form factors. We use two different parameterizations, the usual three-parameter function of $$q^{2}$$ q 2 and the model-independent z-series expansion, to establish a clear understanding of $$q^{2}$$ q 2 dependence. Using the numerical values of the form factors, we predict the branching ratios other physical observables, including forward-backward asymmetries, polarization fractions, etc. of the semileptonic $$B_c$$ B c decays. Subsequently, we predict the branching ratios of two-body nonleptonic weak decays using the factorization hypothesis in self-consistent CLFQM. We also compare our results with those of other theoretical studies.